Empagliflozin in Heart Failure with a Preserved Ejection Fraction - Anker, Stefan D; Butler, Javed; Filippatos, Gerasimos; Ferreira, João P; Bocchi, Edimar; Böhm, Michael; Brunner-La Rocca, Hans-Peter; Choi, Dong-Ju; Chopra, Vijay; Chuquiure-Valenzuela, Eduardo; Giannetti, Nadia; Gomez-Mesa, Juan Esteban; et al. (The New England journal of medicine, 2021)
BACKGROUND: Sodium-glucose cotransporter 2 inhibitors reduce the risk of hospitalization for heart failure in patients with heart failure and a reduced ejection fraction, but their effects in patients with heart failure and a preserved ejection fraction are uncertain. METHODS: In this double-blind trial, we randomly assigned 5988 patients with class II-IV heart failure and an ejection fraction of more than 40% to receive empagliflozin (10 mg once daily) or placebo, in addition to usual therapy. The primary outcome was a composite of cardiovascular death or hospitalization for heart failure. RESULTS: Over a median of 26.2 months, a primary outcome event occurred in 415 of 2997 patients (13.8%) in the empagliflozin group and in 511 of 2991 patients (17.1%) in the placebo group (hazard ratio, 0.79; 95% confidence interval [CI], 0.69 to 0.90; P<0.001). This effect was mainly related to a lower risk of hospitalization for heart failure in the empagliflozin group. The effects of empagliflozin appeared consistent in patients with or without diabetes. The total number of hospitalizations for heart failure was lower in the empagliflozin group than in the placebo group (407 with empagliflozin and 541 with placebo; hazard ratio, 0.73; 95% CI, 0.61 to 0.88; P<0.001). Uncomplicated genital and urinary tract infections and hypotension were reported more frequently with empagliflozin. CONCLUSIONS: Empagliflozin reduced the combined risk of cardiovascular death or hospitalization for heart failure in patients with heart failure and a preserved ejection fraction, regardless of the presence or absence of diabetes. (Funded by Boehringer Ingelheim and Eli Lilly; EMPEROR-Preserved ClinicalTrials.gov number, NCT03057951).
Keywords: dvojitá slepá metoda; Stroke Volume; glukosidy; Glucosides; Benzhydryl Compounds; Sodium-Glucose Transporter 2 Inhibitors; Double-Blind Method; Heart Failure; Chronic Disease; chronická nemoc; benzhydrylové sloučeniny; mužské pohlaví; Adult; tepový objem; Cardiovascular Diseases; ženské pohlaví; Humans; glifloziny; srdeční selhání; Hospitalization; hospitalizace; dospělí; Female; kardiovaskulární nemoci; lidé; Male